2018
DOI: 10.1002/lary.27290
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of gastrostomy tube dependence in surgically managed oropharyngeal squamous cell carcinoma

Abstract: 4. Laryngoscope, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 31 publications
1
20
0
Order By: Relevance
“…Unlike HPV‐negative OPC, HPV‐mediated OPC tends to affect a healthier, younger population with significantly improved survival; as such, potential overtreatment and toxicities play an increased role in treatment decisions, especially for early‐stage disease. With improved survival, functional outcomes such as swallowing function, quality‐of‐life measures, and decreased gastrostomy or tracheostomy dependence are increasingly emphasized . The ideal treatment strategy that optimizes survival and minimizes toxicity is controversial because HPV‐negative OPC treatment paradigms persist as the standard of care.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike HPV‐negative OPC, HPV‐mediated OPC tends to affect a healthier, younger population with significantly improved survival; as such, potential overtreatment and toxicities play an increased role in treatment decisions, especially for early‐stage disease. With improved survival, functional outcomes such as swallowing function, quality‐of‐life measures, and decreased gastrostomy or tracheostomy dependence are increasingly emphasized . The ideal treatment strategy that optimizes survival and minimizes toxicity is controversial because HPV‐negative OPC treatment paradigms persist as the standard of care.…”
Section: Introductionmentioning
confidence: 99%
“…With improved survival, functional outcomes such as swallowing function, quality-of-life measures, and decreased gastrostomy or tracheostomy dependence are increasingly emphasized. 4,5 The ideal treatment strategy that optimizes survival and minimizes toxicity is controversial because HPV-negative OPC treatment paradigms persist as the standard of care. Previous National Cancer Data Base (NCDB) studies not limited to HPV-specific OPC have shown that the use of upfront surgical treatment for OPC has either stayed stable or increased with time.…”
Section: Introductionmentioning
confidence: 99%
“…As such we chose to describe its use in this population which typically requires a relatively low rate of G-tube insertion. Our data does add value to the literature in that there is less reporting of G-tube use in oral cavity cancer patients compared to oropharynx cancer [ 24 , 24 26 , 12 ].…”
Section: Discussionmentioning
confidence: 63%
“…However, these studies are focused primarily on deescalation regimens for "low-risk" patients 23 and patients with surgically managed OPSCC. 24,25 Veterans with OPSCC demonstrate significant differences from the general OPSCC population. The incidence of tobacco exposure in veterans with OPSCC is essentially identical to that of veterans with laryngeal squamous cell carcinoma, surpassing 80%.…”
Section: Introductionmentioning
confidence: 98%
“…However, these studies are focused primarily on deescalation regimens for “low-risk” patients 23 and patients with surgically managed OPSCC. 24,25…”
Section: Introductionmentioning
confidence: 99%